2003
DOI: 10.1021/ja030381r
|View full text |Cite
|
Sign up to set email alerts
|

Constraining Asymmetric Organometallic Catalysts within Mesoporous Supports Boosts Their Enantioselectivity

Abstract: By constraining tethered asymmetric organometallic catalysts within the nanopores of silica supports so as to increase the interaction between the pore wall and the active center (and hence to restrict access of the reactant to the catalyst), a significant improvement in enantioselectivity is achieved. A schematic illustration of a cationic chiral, organometallic catalyst, [Rh(I)(COD)PMP] {(S)-(+)-1-(2-pyrrolidinylmethyl)-pyrrolidine and cyclooctadiene}, which is noncovalently anchored via a N-H...F hydrogen b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(116 citation statements)
references
References 17 publications
(12 reference statements)
5
103
0
8
Order By: Relevance
“…99 % conversion with an enantiomeric excess of 93 % were observed for the reaction of diethyl zinc and 1-naphthaldehyde (1-NaphCHO) in the presence of (15) and an excess of Ti(Oi-Pr) 4 (Tab. 5).…”
Section: Addition Of Diethyl Zinc To Carbonyl Carbon Atomsmentioning
confidence: 99%
See 1 more Smart Citation
“…99 % conversion with an enantiomeric excess of 93 % were observed for the reaction of diethyl zinc and 1-naphthaldehyde (1-NaphCHO) in the presence of (15) and an excess of Ti(Oi-Pr) 4 (Tab. 5).…”
Section: Addition Of Diethyl Zinc To Carbonyl Carbon Atomsmentioning
confidence: 99%
“…For basic principles of asymmetric catalysis in confined space see [14]. [15] features an impressive study of the dependence of enantioselectivity on the pore size of the mesoporous support used. Thus, in an ideal set-up chiral MOFs may connect the advantages of homogeneous stereoselective catalysts with the advantages of heterogeneous catalysis [16].…”
Section: Introductionmentioning
confidence: 99%
“…Using exactly the same approach and anion, Raja et al reported the immobilization of a range of chiral Rh phosphine complexes onto a set of inexpensive, commercially available silicas. [125] The ee values of the asymmetric hydrogenation of methyl benzoylformate were found to increase upon decreasing pore size of the inorganic host, which reflects the beneficial effect of a constrained environment on the enantioselective performance of a chiral catalyst. This method is, in fact, a combination of two immobilization techniques: the triflate ion is hydrogen bonded to the surface hydroxyl groups, and the cationic metal complex is anchored onto this modified surface via an ionexchange step.…”
Section: Noncovalently Bound Metal Complexesmentioning
confidence: 98%
“…For example, cationic Rh(I) complexes containing a chiral diamino ligand and cyclooctadiene have been tethered on mesoporous silica. When used to catalyze the hydrogenation of methyl benzoylformate, enantiomeric excess (EE) values are actually boosted as compared to the homogeneous systems [114,115].…”
Section: Self-assembly Of Functional Organic Molecules On Pore Wallsmentioning
confidence: 99%